The Impact of Political Sophistication and Motivated Reasoning on Misinformation. (2nd September 2020) - Vegetti, Federico; Mancosu, Moreno
ABSTRACT: The debate around political misinformation is gaining increasing relevance among the general and academic audience. If a large body of work is devoted to understanding the mechanisms of diffusion of inaccurate/false news contents (especially on social media), few studies have focused on the individual mechanisms by which people believe in those news. We look at the interplay between two mechanisms: partisan motivated reasoning and political sophistication. While previous literature suggests that political sophisticates are more affected by motivated reasoning, we hypothesize that in the case of character-related misinformation the opposite is true. By using an on-line survey experiment administered to a sample of Italian citizens, we compare the perceived plausibility of real and inaccurate news contents consistent with different political leanings. Our results show that people tend to perceive all partisan-consistent news as more plausible, but political sophisticates are better able to tell real from false news. We conclude that while political information is generally affected by motivated reasoning, political sophistication can effectively reduce citizens' chances to fall for false information.